INFORMAL ARTICLES AND READING-WRITINGSPEAKING CYCLE IN EXTENSIVE READING (ER) PROGRAM: EFL LEARNERS’ PERCEPTION - Umam, Chotibul (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2015)
Informal article is one of authentic materials which may contain valuable informations and extensive input to develop the learners’ language proficiency. Unfortunately, most literature shows that informal articles are not widely used in Extensive Reading (henceforth ER) program. For this reason, in this micro-scale exploratory research, the writer would like to introduce the steps procedure in using informal articles in ERprogram for Indonesian EFL college learners and to investigate their perception toward the implementation of the procedure. The procedure is developed on the basis of the writer’s great interest in creating innovative way in teaching ER at Indonesian collegelevel. The procudure is then called as Reading-Writing-Speaking (RWS) cycle which comprises structured-steps. Although it has some shortcomings, the participants bestow positive perception and respectable comments toward the procedure. The proposedprocedure is expected to be an alternative pathway in teaching ER for English teachers particularly at a university level.